Small-molecule fluorescence-based probes for interrogating major organ diseases - Han, Hai-Hao; Tian, He; Zang, Yi; Sedgwick, Adam C; Li, Jia; Sessler, Jonathan L; He, Xiao-Peng; James, Tony D (Chemical Society reviews, 2021)
Chemical tools that allow the real-time monitoring of organ function and the visualisation of organ-related processes at the cellular level are of great importance in biological research. The upregulation/downregulation of specific biomarkers is often associated with the development of organ related diseases. Small-molecule fluorescent probes have the potential to create advances in our understanding of these disorders. Viable probes should be endowed with a number of key features that include high biomarker sensitivity, low limit of detection, fast response times and appropriate in vitro and in vivo biocompatibility. In this tutorial review, we discuss the development of probes that allow the targeting of organ related processes in vitro and in vivo . We highlight the design strategy that underlies the preparation of various promising probes, their optical response to key biomarkers, and proof-of-concept biological studies. The inherent drawbacks and limitations are discussed as are the current challenges and opportunities in the field. The hope is that this tutorial review will inspire the further development of small-molecule fluorescent probes that could aid the study of pathogenic conditions that contribute to organ-related diseases. This tutorial review describes recent advances involving small molecule fluorescent probes designed to aid in the study of major organ diseases.